Using structural tensors for inelastic material modeling in the finite strain regime – A novel approach to anisotropic damage. (January 2021) - Reese, S.; Brepols, T.; Fassin, M.; Poggenpohl, L.; Wulfinghoff, S.
Abstract: The idea of the paper is to apply the well established structural tensors approach to complex inelastic material modeling in the finite strain regime. Using this concept, a very general and new anisotropic damage model is derived which is the major novel contribution of the paper. In this framework, a second order damage tensor plays the role of a structural tensor. The damage model is coupled to finite elasto-plasticity such that its first purpose is to model damage-induced anisotropy in ductile materials, in particular metals. Further structural tensors could be introduced to represent initial anisotropy of materials such as soft tissues, composites or thermoplastics. The main results of the derivation are the suitable choice of the Helmholtz free energy function, the development of yield and damage potentials as well as the formulation of physically reasonable evolution equations for the plastic deformation, the damage tensor as well as plastic and damage hardening. It is important to mention that all tensorial internal variables are symmetric and referred to the undeformed configuration. To the knowledge of the authors, the interpretation of a structural tensor of the undeformed configuration as damage tensor is new. Two-point tensors such as the plastic part of the deformation gradient show up in the theoretical derivation but are never computed. The plastic spin remains undetermined which has the advantage that a statement about its evolution is not needed. Further, the evolution equation for the plastic deformation includes only six non-linear scalar equations instead of nine. The numerical implementation of the model is straightforward. The number of material parameters remains moderate. A strategy to identify them by means of standard experiments is discussed. Nevertheless, the validation of the model by means of own experiments or experimental results from the literature is left for further work.